The Pragmatics of Fiction: Literature, Stage and Screen Discourse - Locher, Miriam A; Jucker, Andreas H (Edinburgh Textbooks on the English Language - Advanced, 2021)
Drawing on a wide range of fictional texts from Shakespeare and Austen to Game of Thrones and the lyrics of 'We Shall Overcome', this textbook shows how pragmatic analyses can uncover the performative elements that create and shape characters for an audience.